Engaging with Health Markets in Low and Middle‐Income Countries. (April 2014) - Bloom, Gerald; Wilkinson, Annie; Standing, Hilary; Lucas, Henry
Summary: Many low and middle‐income countries have pluralistic health systems with a variety of providers of health‐related goods and services in terms of their level of training, their ownership (public or private) and their relationship with the regulatory system. The development of institutional arrangements to influence their performance has lagged behind the spread of these markets. This paper presents a framework for analysing a pluralistic health system. The relationships between private providers of health services and government, or other organisations that represent the public interest, strongly influence their performance in meeting the needs of the poor. Their impact on the pattern of service delivery depends on how the relationships are managed and the degree to which they respond to the interests of the population. Many governments of low and middle‐income countries are under pressure to increase access to safe, effective and affordable health services. In a context of economic growth, it should be possible to improve access by the poor to health services substantially. Innovations in information technologies and in low cost diagnostics are creating important new opportunities for achieving this. It will be important to mobilise both public and private providers of health‐related goods and services. This will involve big changes in the roles and responsibilities of all health sector actors. Governments, businesses and civil society organizations will need to learn how to make pluralist health systems work better through experimentation and systematic learning about what works and why.